2001
DOI: 10.1177/095632020101200503
|View full text |Cite
|
Sign up to set email alerts
|

Antipoliovirus Flavonoids from Psiadia Dentata

Abstract: The search for antiviral agents against vesicular stomatitis virus, herpes simplex virus type 1 and poliovirus type 2 in plants extracts, led to the isolation of two antipoliovirus flavonoids from the medicinal plant Psiadia dentata (Cass.) DC, Asteraceae: 3-methylkaempferol and 3,4′-dimethylkaempferol. The antipoliovirus activity of both compounds was estimated by comparison with 3-methylquercetin, guanidine and Ro-090179. The most potent inhibitor of poliovirus replication was 3-methylkaempferol, and therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Methoxyflavones and coumarins have been isolated from Psiadia dentata (Fortin et al, 2001;Jakobsen et al, 2001). Robin et al (2001) revealed that 3-methylkaempferol inhibited the genomic RNA synthesis of poliovirus. Aside from this aspect, Psiadia dentata needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Methoxyflavones and coumarins have been isolated from Psiadia dentata (Fortin et al, 2001;Jakobsen et al, 2001). Robin et al (2001) revealed that 3-methylkaempferol inhibited the genomic RNA synthesis of poliovirus. Aside from this aspect, Psiadia dentata needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…231,233 When added at the time of infection, however, both plus-and minus-strand viral RNA synthesis were blocked, but this might be due to the fact that there is not enough genomic RNA to serve as a template to give rise to significant amounts of negative-stranded RNA, detectable by hybridization. 234 Other flavonoids isolated from medicinal plants include two flavonoids from Psiadia dentata (3-methylkaempferol and 3,4 0 -dimethylkaempferol), which are shown to inhibit the synthesis of poliovirus (þ)RNA, 235 and a flavonoid from Pterocaulon sphacelatum, also exhibiting protection against poliovirus-induced CPE formation. 236 Several synthetic flavonoid and isoflavonoid derivatives were evaluated for their potential antipicornavirus activity.…”
Section: -Furylmercury Chloride (2-fmc)mentioning
confidence: 99%
“…Genistein can inhibit the phosphorylations and activations of ATF-2, NF-B and other transcription factors (Evers et al, 2005;Vela et al, 2008). Genistein can also inhibit the phosphorylation of viral proteins and polypeptides (Yura et al, 1993), inhibit viral gene expression and protein function (Kim et al, 2006;Robin et al, 2001), inhibit the tyrosine phosphorylation of viral glycoproteins, (Akula et al, 2002) etc.…”
Section: Discussionmentioning
confidence: 99%